STUDI FINANCIAL MANAGEMENT BEHAVIOR PADA MASYARAKAT SURABAYA - Naila Al Kholilah; Rr. Iramani (STIE Perbanas Surabaya, 2013)
The financial management behavior has become prevailing issue nowadays. This is due to the societys behavior of consumptions in Indonesia, and especially in Surabaya city. This study aims to examine the relationship between Locus of Control, Financial Knowledge, and Income on Financial Management Behavior. The sample consists of 104 respondents, in Su- rabaya in which they were taken by means of Purposive Sampling. The characteristic of re- spondents such as they live in Surabaya, labor force, and they have income equal to Rp 1.500.000. Using Structural Equation Modeling on AMOS, this research found that no direct effect on Financial Management Behavior by Financial knowledge and Income. Locus of Control is positively related to Financial Management Behavior, and Locus of Control medi- ates the effect of Financial Knowledge on Financial Management Behavior.